Integration of Autograph in Improving Mathematical Problem Solving and Mathematical Connection Ability Using Cooperative Learning Think-Pair-Share - Ida Karnasih; Mariati Sinaga (Southeast Asian Mathematics Education Journal, 2015)
The aim of this study was to investigate students’ mathematical problem solving and mathematical connection ability in cooperative learning setting using Dynamic Software Autograph. This experimental study was conducted at high school in learning statistics. The collection of the data was done using observation sheets, documentation, attitude scale, and performance tests. Repeated measure tests were delivered to students for four times. The result of the analysis showed that: (1) Using Dynamic Software Autograph in teachinglearning statistics with cooperative learning Think-Pair-Share improved students’ problem solving and mathematical connection ability; (2) Students’ activity during teaching learning processes continuously improved; (3) The result of analysis of the questionnaire showed that most students like learning statistics using cooperative learning with dynamic software Autograph; (4) Students were very active and showed positive attitude toward learning using cooperative learning Think-Pair-Share using dynamic software Autograph.